PEMBINAAN KARAKTER GOTONG ROYONG DAN KARAKTER INTEGRITAS DALAM UPAYA PEMBIASAAN SISWA SEKOLAH DASAR - Fikriatunnisa; Amelia Nabilla Zahra; Nur Azizah; Dina Selviana; Lanardin; Ika Yatri; Muhammad Azhar Nawawi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Integrity and mutual cooperation are two important principles that educators must instill in children from an early age. The aim of this research is to provide an explanation of the various types of mutual cooperation behavior that can occur, as well as the strategies used by elementary school teachers to help their children develop integrity and the character of mutual cooperation. This research uses a qualitative descriptive research methodology, utilizing observation, interviews and document analysis for data collection. The findings of this study demonstrate the continuation of mutual cooperation education initiatives. However, some children still struggle with teamwork. A teacher can foster a cooperative mindset in his students by providing good examples and giving praise to encourage cooperative behavior. Students with high moral standards and cooperative tendencies are more likely to participate actively in group activities. They also often act in a trustworthy, responsible, and honest manner. The need to incorporate the ideals of honesty and mutual cooperation into the basic education curriculum is emphasized in this research. Community work, collaborative projects, and role-playing can be effective teaching methods to realize this ideal. Teachers are expected to be able to implement these values in their daily interactions with students. Therefore, this study recommends that to deeply instill these values in children from an early age, elementary schools initiate greater character education programs.